Pakistan Army Green Book 2010 : Information Warfare - Pakistan Army; Editorial Board : Brig. Khushnud Iqbal; Col. Tariq Iqbal; Lt. Col. Zafar Iqbal and Major Qamar UI Islam (GHQ, Rawalpindi Pakistan Army, 2010)
Content of the book are the writer' personal views and are not to be taken as official opinion/policy
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals